Clinical, radiological and histopathological correlation in breast lesions: 10 years of experience - Santiago Sanabria, Leopoldo (2025)
Introduction: Breast cancer remains a global public health problem. It is estimatedthat its incidence will increase in the coming years. It is important to evaluatescreening studies in breast clinics through indicators in order to obtain an adequateclinical, imaging and histopathological correlation. Objectives: To evaluate thecorrelation between clinical, radiological and histopathological studies in womenwho underwent breast cancer screening tests over a 10-year period. Methods: Across-sectional, descriptive, retrospective cohort study was conducted using therecords of a referral center from June 2013 to June 2023, of women who underwentbreast cancer screening. In those who underwent biopsy, the samples were analyzedat our institution. Results: The records of 6 754 women who met the inclusion criteriawere analyzed, where the average age of the study population was 50.7 years. It wasrecorded that 73.2% of the studies were categorized BI-RADS 2 and the majority ofthe participants were asymptomatic. Of those 551 women who received a BI-RADS>4 mammogram, 226 (41%) had a malignant result. Conclusions: Mammographyhas been shown to be the only imaging tool that has managed to have an impacton mortality. There are modalities, such as tomosynthesis, that have increasedthe performance of this test. It is valid to use new technologies to maintain qualitystandards in the studies.